2015
DOI: 10.13080/z-a.2015.102.057
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of isoflavones in red clover (Trifolium pratense L.) at flowering stage

Abstract: The objective of this study was to determine the concentrations of isoflavones in the cultivars and ecotypes of red clover (Trifolium pratense L.) in a whole above ground part of a plant and separately in stems, leaves and flowers at flowering stage. Isoflavones were extracted using acidified aqueous methanol and subsequent analyses of the extracts were carried out by ultra-performance liquid chromatography coupled with a photodiode array detector. Red clover accumulated the highest concentrations of formonone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 23 publications
4
33
0
Order By: Relevance
“…Among the legume species discussed in the current paper only isoflavones present in red clover have been quantified fairly in detail (Lemežien_ e et al 2015;Ramos et al 2008;Saviranta et al 2008). The concentration of total isoflavones we found in red clover (19.6 mg/g) agrees with the range reported by Ramos et al (2008) and Saviranta et al (2008) (12.3-24.1 and 15.5-24.1 mg/g, respectively).…”
Section: Phytoestrogenssupporting
confidence: 89%
See 1 more Smart Citation
“…Among the legume species discussed in the current paper only isoflavones present in red clover have been quantified fairly in detail (Lemežien_ e et al 2015;Ramos et al 2008;Saviranta et al 2008). The concentration of total isoflavones we found in red clover (19.6 mg/g) agrees with the range reported by Ramos et al (2008) and Saviranta et al (2008) (12.3-24.1 and 15.5-24.1 mg/g, respectively).…”
Section: Phytoestrogenssupporting
confidence: 89%
“…Data were collected and managed using the HyStar 3.2 software (Bruker). Analytes in the extracts were identified according to our recently published procedure (Lemežien_ e et al 2015;Taujenis et al 2016). Quantification was performed by external calibration and the results were expressed in mg per 1 g of the dry matter (mg/g).…”
Section: Quantification Of Phytoestrogensmentioning
confidence: 99%
“…There is evidence to suggest that Astragalus species have more bioactive compounds related to isoflavones than the four isoflavones selected for quantification in this study. Among the perennial legume species, isoflavones have only been quantified in some detail in red clover [ 30 , 45 , 46 ], and to a much lesser extent in other Trifolium spp. [ 47 , 48 ] and Medicago spp.…”
Section: Resultsmentioning
confidence: 99%
“…Low levels of total isoflavones and most of the individual isoflavones were also determined in the breeding populations Rc-13/40, Rc-15/12, and Rc-15/7. Lemeziene et al (2015). These widely different results may be explained by the fact that a total isoflavone content and the content of individual isoflavones depend on many other factors in addition to a cultivar, such as a farm management, harvest timing and growing seasons, plant phenological stages, plant parts, growth conditions, sampling methodology, climatic conditions, preservation method and storage.…”
Section: Proportion (%) Of Individual Isoflavones In the Total Amountmentioning
confidence: 99%
“…Prosječni sadržaj izoflavona (μg g -1 suhe tvari) u listovima crvene djeteline. , 2199.02-15670.39 μg g -1 of DM for biochanin A, 14.70-516.91 μg g -1 of DM for genistein, 0-137.91 μg g -1 of DM for daidzein, and 9810-36360 μg g -1 of DM for total isoflavones Lemeziene et al (2015). determined the isoflavone values in the Lithuanian red clover cultivars and ecotypes and found that their contents in the leaves…”
mentioning
confidence: 99%